Problematika dalam Evaluasi Studi Pembelajaran Pendidikan Islam - Ruqoiyah Ruqoiyah (MOMENTUM : Jurnal Sosial dan Keagamaan, 2022)
Abstract: Islamic educational institutions such as madrasas and Islamic boarding schools have succeeded in building human character with a religious culture that loves the Republic of Indonesia. The slanted view of informal institutions "madrasas and Islamic boarding schools" since its establishment until now still exists. They feel that the output or alumni of informal institutions are less ogled by the national job market, especially internationally. In fact, until now Islamic educational institutions still exist and do not care about these unfounded accusations. Islamic educational institutions are more focused on strengthening and deepening the competence of santri, students, and prospective scholars so that after returning to society they reflect individuals who have character, integrity, broad knowledge, and virtuous character. The method used is descriptive qualitative. While the approach used in literature. The results of the analysis found the following findings that Islamic Education policies from time to time experienced quite heavy dynamics. Dutch-era Islamic education received policy discrimination. Islamic education only got a breath of fresh air after the Dutch leadership fell to Japan. The Japanese government agreed to the request of the Indonesian people. Starting from the establishment of Elementary Schools, Middle Schools, and Senior High Schools, to the establishment of Islamic Colleges in Jakarta. The journey of Islamic education can be said to have truly become independent after Indonesia's independence. There are five problems to evaluate the study of Islamic Education in Indonesia, including Limitations of Government Power, Disagreements on a Problem, Subjectivity in Interpretation, Limitations in Research on Resource Management, and Complexity of Human Behavior. These five problems need to get responses from various parties, it is not enough if they are only handled by a few people, it is necessary for the cooperation of all parties so that ideal policies can be formulated in time.